Carbon Nanotubes Coating for Micropunch - Guo, Kelvii Wei (Journal of Coating Science and Technology, 2022)
The multi-walled carbon nanotubes (MWCNTs) were coated on micropunch homemade equipment with the waste alcohol as a resource. The correlated characteristics were evaluated by scanning electron microscopy (SEM), transmission electron microscope (TEM), and Raman spectroscopy. Moreover, the synthesized MWCNTs were grown on some micropunches to confirm the relevant, beneficial effect on the service life of micropunches compellingly and convincingly. The results indicate that MWCNTs coated on micropunch can enhance its service life up to 35% of that without MWCNTs. Due to the lubrication of MWCNTs coating between the micropunch and the specimen, the wear of the micropunch coated with MWCNTs distinctively decreases, even in the severe wear period. As a result, the correlated wear loss is also less than that of the micropunch without MWCNTs coating, ascribed to the graphitic nature of MWCNTs. Meanwhile, because of the usage of the waste alcohol, the technique of the relevant synthesized MWCNTs is green to the environment, which is promising for practical applications.